Answers

2015-06-09T22:16:31+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
We can factor out 4 so:
4y²+4y-8 = 4(y²+y-2)
Now we need to factor out y²+y-2

Method 1:
We check the factors of 2 which should have a difference of 1, and they do. They are 1 and 2. So: y²+y-2 = (y+2)(y-1)

Method 2: Quadratic Formula
x = -1 ± √(1²+8) = -1 ± √9 = -1 ± 3 = -2 or 1
              2               2            2
So: y
²+y-2 = (y+2)(y-1)

Therefore, 4y²+4y-8=4(y+2)(y-1)
1 5 1